Perkembangan Cacing Pontoscolex corethrurus Pada Media Kultur dengan Berbagai Jenis Tekstur Tanah dan Bahan Organik - Andi Andi; Tengku Sabrina; Mariani Sembiring (Universitas Sumatera Utara, 2017)
Application of Pontoscolex corethrurus gives the positive effect to soil properties. Recently, P.corethrurus is directly collected from field which are time consuming and costly. This research aimed to determine the best organic matter and soil texture types as the artificial culture medium in supporting the P.corethrurus growth. This research was conducted in Ecological and Biological Laboratory, Agriculture Faculty, University of Sumatera Utara. This research was conducted in two phases, with using factorial randomized block design. The first factor was types of soil texture i.e. sandy loam (60% sand; 24% silt; 16% clay), Clay (28% sand; 20% silt; 52% clay), clay loam (36% sand; 28% silt; 36% clay). The second factor was types of organic matter i.e. without organic matter, cow manure, sheep manure, and hevea leaf litter. The result showed that in both phases of experiment the best soil texture types in increasing earthworm biomass and cocoon number of P.corethrurus was sandy loam, following with treatment on texture clay loam, and clay respectively. The best organic matter treatments in increasing earthworm biomass and cocoon number of P.corethrurus in phase 1 was sheep manure, cow manure, Hevea leaf litter, and without organic matter respectively. Application of sheep manure on sandy loam soil and application of sheep manure on clay soil had the same potency in increasing P.corethrurus biomass only in first phase experiment. Keywords : Culture medium, Earthworm application, Organic matter, Pontoscolex corethrurus, Soil texture